Low temperature initiation by methylene bis(diethyl malonate)–Ce(IV) redox system in organic solvents - Bıçak, Niyazi; Özeroğlu, Cemal (Elsevier BV, 2001)
Abstract Methylene bis(diethyl malonate)–cerium ammonium nitrate redox couple serves as initiator in triethyl phosphate for polymerization of methyl methacrylate at room temperature. High polymerization yield (>90%) can be attained at moderate concentration ratios (monomer/initiator ≅70:1) in 4 h reaction periods. Increasing molar ratio of methylene bis(diethyl malonate) to cerium salt causes to low molecular weights which implies possibility of its chain transfer effect through active methylene groups at the same time.